Preferential Budding of Vesicular Stomatitis Virus from the Basolateral Surface of Polarized Epithelial Cells Is Not Solely Directed by Matrix Protein or Glycoprotein - Drokhlyansky, Eugene (J Virol, 2015)
Vesicular stomatitis virus has been shown to bud basolaterally, and the matrix protein, but not glycoprotein, was proposed to mediate this asymmetry. Using polarized T84 monolayers, we demonstrate that no single viral protein is sufficient for polarized budding. Particles are released from the apical and basolateral surfaces and are indistinguishable, indicating that there is no apical assembly defect. We propose that aspects of host cell polarity create a more efficient budding process at the basolateral surface.